Estrategias de enseñanza y logro de aprendizajes en el área de matemática en estudiantes del séptimo ciclo de secundaria en la IE Padre Severino Deshaies Fernando Lores 2021 - Bardales Baneo, Rudy Marvin (2024)
The main objective of the present study has been to determine the relationship between teaching strategies and learning achievement in the area of mathematics in students of the seventh cycle of secondary school in the I.E. Father Severino Deshaies, Fernando Lores District 2021. To achieve the objective, the type of relational research was considered, through procedures designed such as field, transversal and bivariate. For the study, the population was made up of 113 students, who were also the sample. In order to collect the data, there was a questionnaire and a learning achievement collection sheet, which were validated by experts. The techniques used were the survey and documentary analysis. The Pearson rating coefficient, with a value of 0,534; indicates a relationship that exceeds moderate, indicating that the implementation and improvement of teaching strategies are associated with a corresponding increase in mathematical learning achievement. The statistical significance of this relationship is confirmed with a p value less than 0,05; suggesting that the observed classification is not a result of chance. Furthermore, the scatter plot exhibits a positive linear trend, visually illustrating that increases in the use of effective teaching strategies are linked to improvements in students' mathematical performance.